2021
DOI: 10.7860/jcdr/2021/50990.15425
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Musculoskeletal Disorders among Recent Dental Graduates in Saudi Arabia: A National Survey

Abstract: Introduction: Musculoskeletal Disorders (MSDs) are one of the most prevalent occupational hazards affecting dental professionals. Aim: To assess the prevalence and associated risk factors of MSDs among recent dental graduates in Saudi Arabia and evaluates their practice of ergonomics as well as the impact of MSDs on their daily activities. Materials and Methods: This cross-sectional study was carried out among all dental interns (n=1552) who graduated from dental schools in Saudi Arabia in the academic year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In the present study, we found some encouraging results that half of the dental professionals indulged in physical activities regularly while in another survey conducted 8 2/3 r d of the dentists regularly indulged in activities and similar results were seen in Kierklo et al observation while contrast results were seen 19 where 48.6% individuals were not indulged in physical activities.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we found some encouraging results that half of the dental professionals indulged in physical activities regularly while in another survey conducted 8 2/3 r d of the dentists regularly indulged in activities and similar results were seen in Kierklo et al observation while contrast results were seen 19 where 48.6% individuals were not indulged in physical activities.…”
Section: Discussionsupporting
confidence: 85%